2021
DOI: 10.1111/glob.12321
|View full text |Cite
|
Sign up to set email alerts
|

Labour market integration and transnational lived citizenship: Aspirations and belonging among refugees in Germany

Abstract: Transnational lived citizenship has gained prominence as a means to analyse mobility and foreground activist notions of citizenship over legal status. I argue that lived citizenship and transnational movements are strongly intertwined with aspirations and belonging. I use the material example of labour market integration as the space of enactments of citizenship and analyse the patterns of belonging those create and contest. I develop my argument through the empirical example of labour market integration of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…This terminology is supported by recent debates on transnational lived citizenship that, on the one hand, aim to foreground non‐state‐based connections and conceptions of belonging, while at the same time recognize that the nation state remains a powerful means of identification, belonging and conditioner of lived citizenship (see Horst et al., 2020; Kallio & Mitchell, 2016; Kallio et al., 2020; Müller, 2022).…”
Section: Theoretical Lens: Transnational Lived Citizenshipmentioning
confidence: 98%
See 2 more Smart Citations
“…This terminology is supported by recent debates on transnational lived citizenship that, on the one hand, aim to foreground non‐state‐based connections and conceptions of belonging, while at the same time recognize that the nation state remains a powerful means of identification, belonging and conditioner of lived citizenship (see Horst et al., 2020; Kallio & Mitchell, 2016; Kallio et al., 2020; Müller, 2022).…”
Section: Theoretical Lens: Transnational Lived Citizenshipmentioning
confidence: 98%
“…Although these authors also recognize the perhaps problematic orientation towards the nation-state inherent in the word transnationalism (see also Krawatzek & Müller-Funk, 2020), I contend that the term transnational is still useful to understand flows and connections between and beyond nation states, with cities a pertinent focus of reference (Kemp & Müller, 2021), as it allows us to analyse lived realities of migrants across a transnational social field. This terminology is supported by recent debates on transnational lived citizenship that, on the one hand, aim to foreground non-state-based connections and conceptions of belonging, while at the same time recognize that the nation state remains a powerful means of identification, belonging and conditioner of lived citizenship (see Horst et al, 2020;Kallio & Mitchell, 2016;Kallio et al, 2020;Müller, 2022).…”
Section: Theoretical Lens: Transnational Lived Citizenshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Collyer (2017: 576-577) has suggested that the reason why transnational theorisation has had relatively little impact on studies on citizenship is due to the territorial bias, which "associate citizenship primarily, if not exclusively, with belonging to a particular territory". However, more recent conceptualisations of lived citizenship situate it in the transnational frame and push towards conceptualisations of transnational lived citizenship (Kallio and Mitchell, 2016;Martin and Paasi, 2016;Müller, 2022;Müller and Belloni, 2021). Instead of approaching citizenship merely as right-based status linked to a nation-state, the transnational lived citizenship approach "enables us to look at the intersections between formal and aspirational aspects of citizenship combined, and its emotional and practical aspects -those aspects defined by feelings of belonging, transnational attitudes, and circulation of material cultures."…”
Section: Problematising Migrancy In Citizenshipmentioning
confidence: 99%
“…Throughout my analysis of these specific cases, I look into the extent to which melancholia and despair govern refugee identification. The representation of the struggle of misintegration and the lack of assimilation reinforces the discourse of disobligingness, implying that the refugee subject is one that does not belong and ought not to feel welcome in whichever host country that can grant them asylum (Müller, 2022). The asylum at hand is depicted as contrary to the romanticized homeland which was the primary site of belongingness.…”
Section: Debriefing Monumentationmentioning
confidence: 99%